PENENTUAN ESTIMASI PARAMETER REGRESI DENGAN VARIABEL DEPENDEN TERSENSOR - L., Ignasia Diana; Dwi, Ispriyanti (MATEMATIKA, 2008)
Regression analysis is a statistical analysis that use relation between two or more variables. To use regression analysis, the value of each variable (dependent or independent) must be available. In fact, not all of Â the information is available. Missing value on dependent variable cause Ordinary Least Square is no longer to be used. One method to handle this problem is censored regression. On this regression, missing value is replaced with a censored point. This censored point may occur naturally orÂ made by researcher, depend on the goal of research. Maximum Likelihood Method following Newton-Raphson Iteration Method, is used to get parameter estimation of censored regression. Test of model signification uses Likelihood Ratio-test and Wald-test. Â